2020
DOI: 10.1590/s1517-707620200003.1084
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades térmicas de compósitos de acrilonitrila-butadieno-estireno (ABS) e fibras de celulose modificadas com nanopartículas de sílica (SiO2)

Abstract: RESUMO O objetivo deste trabalho foi caracterizar os compósitos produzidos com o terpolímero acrilonitrila-butadieno-estireno (ABS) reforçados com fibras de polpa celulose modificadas com nanopartículas de sílica (SiO2). Primeiramente, as fibras foram modificadas utilizando o processo sol-gel, tendo como precursor da sílica o ortosilicato de tetraetila (TEOS). Adicionalmente, duas concentrações de TEOS e dois tempos de reação foram utilizados para produzir dois tipos de fibras modificadas, FT1 e FT2, logo depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%